2017
DOI: 10.3947/ic.2017.49.1.44
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Lipid Profile Changes in Pediatric Patients with Acute Mononucleosis

Abstract: BackgroundAcute Epstein-Barr virus (EBV) infection could lead to atherogenic lipid profile changes in adults; while there is no evidence about the children with Infectious mononucleosis (IM). The aim of this study was to evaluate the lipid profile of the children in acute phase of mononucleosis and two months after the recovery.Materials and MethodsFrom 2010 through 2012, 36 children with IM aged 1-10 years were enrolled in a prospective cross-sectional study. Fasting serum total cholesterol, high density lipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…More recently, Apostolou et al found atherogenic lipid changes in 29 patients with infectious mononucleosis; an increase in serum triglyceride concentrations was associated with an increase in the concentrations of apolipoprotein C-III, which is an inhibitor of lipoprotein lipase [22]. Likewise, Sayyahfar et al reported transient hypertriglyceridemia in 36 children with infectious mononucleosis [23]. In this article, we report on an adult patient with extreme hypertriglyceridemia during infectious mononucleosis.…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…More recently, Apostolou et al found atherogenic lipid changes in 29 patients with infectious mononucleosis; an increase in serum triglyceride concentrations was associated with an increase in the concentrations of apolipoprotein C-III, which is an inhibitor of lipoprotein lipase [22]. Likewise, Sayyahfar et al reported transient hypertriglyceridemia in 36 children with infectious mononucleosis [23]. In this article, we report on an adult patient with extreme hypertriglyceridemia during infectious mononucleosis.…”
Section: Introductionmentioning
confidence: 61%
“…The lipid paradox is not limited to lymphoproliferative and hemophagocytic syndromes but is also observed in other immunebased disorders [19,20]. [23]. In this article, we report on an adult patient with extreme hypertriglyceridemia during infectious mononucleosis.…”
Section: Introductionmentioning
confidence: 85%
“…Epstein–Barr virus infection leads to an increase in blood triglyceride levels, which is considered to be strongly associated with systemic immune inflammation in addition to being associated directly with liver function impairment. Similarly, Sayyahfar et al found elevated blood triglyceride levels in patients with acute EBV infection, possibly because changes in blood triglyceride levels and lipoprotein metabolism during infection led to anti‐inflammatory effects, thereby contributing to host defense, and such changes were a part of the acute phase response of the innate immune system 23 . In some children with acute EBV infection, elevated blood triglyceride levels recovered 2 months after the infection, and most lipid metabolism abnormalities recovered 4 months after the infection.…”
Section: Discussionmentioning
confidence: 95%
“…Similarly, Sayyahfar et al found elevated blood triglyceride levels in patients with acute EBV infection, possibly because changes in blood triglyceride levels and lipoprotein metabolism during infection led to anti-inflammatory effects, thereby contributing to host defense, and such changes were a part of the acute phase response of the innate immune system. 23 In some children with acute EBV infection, elevated blood triglyceride levels recovered 2 months after the infection, and most lipid metabolism abnormalities recovered 4 months after the infection. Blood triglyceride levels may be used as an indicator of recovery from EBV infection.…”
Section: Discussionmentioning
confidence: 98%
“…More recently, Apostolou et al observed atherogenic lipid changes in 29 patients with infectious mononucleosis, such as increased serum triglyceride (TG) concentrations [ 7 ]. Likewise, Sayyahfar et al reported transient hypertriglyceridemia in 36 children with infectious mononucleosis [ 8 ].…”
Section: Introductionmentioning
confidence: 99%